An existence theorem for an analytic first order PDE in the framework of Colombeau's theory - Aragona, J.; Soares, M. (Springer, 2001)
We study the existence of a holomorphic generalized solution u of the PDE[GRAPHICS]where f is a given holomorphic generalized function and (alpha (1),...alpha (m)) is an element of C-m\{0}.
Keywords: holomorphic generalized functions; strictly pseudoconvex open set; generalized numbers